Проблема раціоналізації політичної діяльності - Абизова, Л. В.; Abyzova, L. V.; Ємельяненко, Ганна Дмитрівна; Ємельяненко, Г. Д.; Yemelianenko, Hanna D.; Степанов, В’ячеслав Володимирович; Степанов, В. В.; Stepanov, Viacheslav V. (Одеса, 2021)
У статті розглядається структура та механізм політичної діяльності, досліджується політичний інтерес як основна детермінанта політичної діяльності, можливі шляхи і механізми реалізації політичних інтересів. Наголошено на тому, що політичний інтерес визначає дії суб’єктів політики і є вирішальним мотивом, що мобілізує суб’єкта політики боротися за збереження або зміну наявних умов і форм його політичної діяльності. Виникнення політичного інтересу зумовлює формування у суб’єкта політики певної політичної мети і вимагає від нього дій, спрямованих на її досягнення. Зазначено, що в науковій літературі розрізняють політичний інтерес у широкому і вузькому значенні слова. У широкому розумінні політичний інтерес є усвідомленням об’єктивних можливостей реалізації суспільством або групами своїх специфічних інтересів за допомогою політичної влади. У вузькому сенсі політичний інтерес є усвідомленням суб’єктами об’єктивної можливості участі у здійсненні політичної влади. У статті зафіксовано різноманітні види політичних інтересів з урахуванням ієрархії їх впливу на політичну діяльність: загальнодержавні або загальнонаціональні, інтереси різних політичних груп, інтереси окремих політичних лідерів, міждержавні політичні інтереси. Зроблено висновок про те, що сформований політичний інтерес перетворюється на мету діяльності. Політична ситуація припускає різні шляхи реалізації політичних цілей або актуалізує деякі з них. У політичній ситуації узгоджуються або протиставляються політичні інтереси, що призводить до коригування цілей. Суб’єкт політичної діяльності в конкретній ситуації може реалізувати одну, дві або набір цілей. Виникає так зване «дерево цілей», у якому суб’єкт обирає найбільш можливі до реалізації в цій ситуації. Вибір цілей залежить від узгодження політичних інтересів, моральних норм і зумовлює політичну відповідальність.

The article analyzes the structure and mechanism of political activity, it examines a political interest as the main determinant of political activity, possible ways and mechanisms of realization of political interests. The authors emphasize that the political interest determines the actions of political actors, it serves as a crucial motive mobilizing the political actor to fight for the preservation or change of existing conditions and forms his/her behavioural strategies in politics. The emergence of the political interest determines the formation of the political subject’s particular political goal and requires him/ her to take action to achieve it. It is noted that there are broad and narrow approaches to the understanding of political interests in the scientific literature. In the broad sense, political interest is an awareness of the objective possibilities of society or social groups to realize their specific interests with the help of political power. In the narrow sense, political interest is an awareness of the objective possibility of participation in the implementation of political power by the political subjects. Political interests can be classified according to various criteria: according to generality (personal and group), according to the sphere of functioning (domestic and foreign policy), according to the nature of the subject (national and state), according to the possibility of implementation (real and imaginary). In the article, the political interests are classified according to the consideration of the hierarchy of their influence on political activity. Therefore, the following types of political interests are under investigation: a) national or state; b) the interests of different political groups; c) the interests of individual political leaders; d) the political interests in interstate relations. It is concluded that the formed political interest becomes the purpose of the activity. The political situation allows different ways of achieving political goals or actualizes some of them. At the same time, in a political situation, political interests are coordinated or opposed in a special way, this coordination or opposition leads to the correction of the goals. The subject of political activity in a particular situation may realize one, two or a set of goals. There is the so-called “tree of goals”. Facing the “tree of goals” the subject chooses the most possible for implementation, achievement in this situation purposes. The choice of possible goals for implementation depends on the system of coordination of political interests, executes under the control of generally accepted moral norms and determines political responsibility.
Абизова Л. В. Проблема раціоналізації політичної діяльності / Л. В. Абизова, Г. Д. Ємельяненко, В. В. Степанов // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2021. - Вип. 31. - С. 84-88. DOI https://doi.org/10.32837/apfs.v0i31.1008
Keywords: політика; політична діяльність; політичний інтерес; влада; політичне рішення; політичний вибір; politics; political activity; political interest; power; political decision; political choice; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science